1997
DOI: 10.1128/jvi.71.12.9150-9156.1997
|View full text |Cite
|
Sign up to set email alerts
|

Rous sarcoma virus direct repeat cis elements exert effects at several points in the virus life cycle

Abstract: Two ϳ135-nucleotide (nt) direct repeats flank the Rous sarcoma virus (RSV) oncogene src and are composed of two smaller repeats, dr1 (ϳ100 nt) and dr2 (ϳ36 nt). These sequences have been reported to contain cis-acting signals necessary for RNA packaging and elements that allow cytoplasmic accumulation of unspliced RNA (cytoplasmic transport elements). In this report, we show that avian fibroblasts infected with the Prague A strain of RSV with precise deletions of both dr1 elements express src and are transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 32 publications
6
31
1
Order By: Relevance
“…ALV particle assembly also appears to be modulated by RNA nuclear export, and mutations in the CTE can lead to defects in assembly and gRNA packaging (66)(67)(68)(69). In addition, mammalian cells are nonpermissive for ALV replication with multiple restrictions being evident including Traffic 2006; 7: 1440-1450 virion production [(70) and references within].…”
Section: Connections Between Grna Nuclear Export and Virion Assemblymentioning
confidence: 99%
“…ALV particle assembly also appears to be modulated by RNA nuclear export, and mutations in the CTE can lead to defects in assembly and gRNA packaging (66)(67)(68)(69). In addition, mammalian cells are nonpermissive for ALV replication with multiple restrictions being evident including Traffic 2006; 7: 1440-1450 virion production [(70) and references within].…”
Section: Connections Between Grna Nuclear Export and Virion Assemblymentioning
confidence: 99%
“…5A) shows that there are only 34 nucleotides between the end of the env coding region and the polypurine tract. This is in contrast to the 5Ј UTRs of ALSVs, which are between 200 and 350 bp in length and which contain an approximately 150-bp sequence called the direct repeat that is required for efficient RNA transport to the cytoplasm (42,43) and RNA stability and/or Gag assembly (51,52). There is no evidence for a direct repeat in ev/J proviruses.…”
Section: Structure Of Ev/j Proviruses In Phage Genomic Clonesmentioning
confidence: 97%
“…Since these two DR sequences are over 80% homologous (Ogert et al, 1996), it has been suggested that their functions are redundant. When DR point mutations are present in viral clones bearing a single DR, these clones are replication-defective (Sorge et al, 1983;Simpson et al, 1997Simpson et al, , 1998Ogert and Beemon, 1998;Aschoff et al, 1999). The DRs also play an intergral role in the stability of the unspliced RNA (Ogert et al, 1996;Simpson et al, 1997Simpson et al, , 1998.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that the DRs mediate the nuclear export of unspliced viral RNAs (Ogert et al, 1996;Ogert and Beemon, 1998;Simpson et al, 1997Simpson et al, , 1998Yang and Cullen, 1999;Paca et al, 2000), although this notion is not unanimously accepted. It has been suggested that the DRs function only in the cytoplasm, facilitating the viral packaging of genomic RNA (Sorge et al, 1983;Aschoff et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation